2011 IEEE International Conference on RFID-Technologies and Applications 2011
DOI: 10.1109/rfid-ta.2011.6068632
|View full text |Cite
|
Sign up to set email alerts
|

Efficient self-adjusting, similarity-based location fingerprinting with passive UHF RFID

Abstract: Abstract-In this paper we present extensive experimental results of location fingerprinting with passive UHF radio-frequency identification (RFID). As recent passive RFID hardware provides information about received signal strength (RSS), we evaluate its usefulness in the context of fingerprinting based on classical vector similarity measures. We analyze the impact of decisive parameters of the applied approach and also select them automatically via cross-validation, including the most appropriate similarity m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…These approaches estimate the position of a mobile agent from a set of precollected observations. They showed a slight improvement to model-based approaches [9]. However, the concern of this paper is mapping of RFID tags, which requires an explicit sensor model and it is almost impossible to take all environmental factors into account.…”
Section: Mapping Rfid Tagsmentioning
confidence: 99%
See 1 more Smart Citation
“…These approaches estimate the position of a mobile agent from a set of precollected observations. They showed a slight improvement to model-based approaches [9]. However, the concern of this paper is mapping of RFID tags, which requires an explicit sensor model and it is almost impossible to take all environmental factors into account.…”
Section: Mapping Rfid Tagsmentioning
confidence: 99%
“…Furthermore, location-specific factors, such as the materials the tags are attached to, obstacles in the environment, orientation between tag and antenna or other radio devices in the environment, have high influence on the behavior of the RFID reader. Thus, many authors applied location-fingerprinting techniques to improve the localization accuracy of mobile agents [9], [10]. These approaches estimate the position of a mobile agent from a set of precollected observations.…”
Section: Mapping Rfid Tagsmentioning
confidence: 99%
“…In the first case, we test the filters by the TWOR circular trajectory in an indoor space with a constant motor displacement and measurement noise. In the second case, all filters are tested by experimental data available from [30].…”
Section: Self-localization In Rfid-tag Environmentsmentioning
confidence: 99%
“…In this paper, it is necessary to find a reliable similarity measurement function to match the speed estimated by RFID due to the large number of clusters obtained by laser sensors. Vorst et al [ 34 , 35 ] compared different similarity algorithms in order to achieve self-localization with passive RFID fingerprints. They showed that the Bray–Curtis (BC) measure gives the best performance among all of the evaluated methods.…”
Section: Indoor Multiple Dynamic Objects Identification and Localimentioning
confidence: 99%